NSB Global Enterprise / Nor Alia Shahira Anas - Anas, Nor Alia Shahira (2020)
NSB Global Enterprise is a sole trader company which located at Kuala Lumpur and has been operated since 29th January 2020. This company focus on selling the travelling appliance techno product. TF Luggage is a main product in NSB Global Enterprise.